Modified fusible polytetrafluoroethylene and preparation method thereof
Macroscopic polytamononhene and composite nano -nano -nanoxide after liquid nitrogen low temperature crushing treatment and dopamine surface modification are covered with high temperature coverage, which solves the problem of lack of wear resistance and local discharge resistance, and significantly improves mechanical performance. Personal life.
Patent Information
- Application Number
- CN202411470309.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fusible polytetrafluoroethylene has poor wear resistance, easy to lose, short service life, and the nano-silica is prone to agglomeration and affecting the processing process, and the adhesive performance is poor between the nano-silica.
By crushing the melting polyticolytic ethyl -fluorine vine -liquid nitrogen, increase the surface ice crystals and improve dispersability, and then use dopamine surface modification and complex mixing to form a shielding layer to improve local discharge performance. Subsequently, high -temperature covering with composite nano -nanotoxide to enhance binding and improve mechanical properties.
The wear resistance, partial discharge resistance and mechanical properties of modified fusible polytetrafluoroethylene are significantly improved, extending its service life and expanding its application scope.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polytetrafluoroethylene modification, and in particular relates to a modified fusible polytetrafluoroethylene and a preparation method thereof. Background Art
[0002] As a special engineering plastic, polytetrafluoroethylene (PTFE) is widely used in many fields. It has good acid and alkali resistance, solvent resistance, high and low temperature resistance, weather resistance and other properties. Most importantly, compared with other materials, polytetrafluoroethylene has a lower friction coefficient and can be used as a good sealing material. Fusible polytetrafluoroethylene (PFA) is a copolymer of tetrafluoroethylene (TFE) and a small amount of perfluoroalkyl vinyl ether (PAVE), and is an important type of fluorine-containing polymer. The unique small size effect, surface effect and macroscopic quantum tunneling effect of ultrafine powders cause nano-silicon dioxide to easily agglomerate in the air and liquid media, which seriously affects the processing of nano-silicon dioxide modified fusible polytetrafluoroethylene. Therefore, it is necessary to coat the ultrafine powder to obtain new physical, chemical and other functions on the particle surface, thereby improving the dispersibility of the particles during the modification process and the compatibility with other substances.
[0003] At present, fusible polytetrafluoroethylene has poor wear resistance and partial discharge resistance, is easy to wear, and has a short service life, which limits its scope of application; although mixing polytetrafluoroethylene with nano-silicon dioxide can improve the optical, thermal, electrical, magnetic, and catalytic properties of polytetrafluoroethylene, silicon dioxide is prone to agglomeration, which will affect the processing of modified fusible polytetrafluoroethylene; the surface energy of fusible polytetrafluoroethylene powder is low and the crystallinity is large, so it is difficult for molecular chains to diffuse and entangle with each other, resulting in poor adhesion between polytetrafluoroethylene and nano-silicon dioxide, making the coated nano-silicon dioxide easy to fall off. Summary of the invention
[0004] The present invention provides a modified fusible polytetrafluoroethylene and a preparation method thereof. The fusible polytetrafluoroethylene is subjected to low-temperature pulverization treatment with liquid nitrogen to obtain pulverized fusible polytetrafluoroethylene; after the fusible polytetrafluoroethylene is subjected to low-temperature pulverization treatment with liquid nitrogen, the material containing ice crystals on the surface of the fusible polytetrafluoroethylene is easily pulverized, and it is easier to obtain fusible polytetrafluoroethylene powder with finer particle size and good dispersibility; the pulverized fusible polytetrafluoroethylene in the surface modification step S1 of dopamine is mixed with a compound to obtain a fusible polytetrafluoroethylene composition; the compound can be modified on the surface of dopamine by chemical bond grafting A shielding layer is formed on the fusible polytetrafluoroethylene to prevent charge accumulation of the fusible polytetrafluoroethylene, which causes local discharge breakdown and damages the fusible polytetrafluoroethylene, thereby improving the local discharge resistance of the fusible polytetrafluoroethylene and enhancing the bonding force between the nano-silicon dioxide and the polytetrafluoroethylene powder; the composite nano-silicon dioxide and the fusible polytetrafluoroethylene composition in step S2 are coated at high temperature to finally obtain modified fusible polytetrafluoroethylene; the pyrogallol-polyethyleneimine polymer improves the lubricity of the modified fusible polytetrafluoroethylene, further improves its interface bonding force, and overall improves the comprehensive performance of the modified fusible polytetrafluoroethylene.
[0005] Technical problems to be solved by the present invention: At present, fusible polytetrafluoroethylene has poor wear resistance, is easy to wear, and has a short service life, which limits its scope of application; although mixing polytetrafluoroethylene with nano-silicon dioxide can improve the optical, thermal, electrical, magnetic, catalytic and other properties of polytetrafluoroethylene, silicon dioxide is prone to agglomeration, which will affect the processing of modified fusible polytetrafluoroethylene; fusible polytetrafluoroethylene powder has low surface energy and high crystallinity, and it is difficult for molecular chains to diffuse and entangle with each other, resulting in poor adhesion between polytetrafluoroethylene and nano-silicon dioxide, making the coated nano-silicon dioxide easy to fall off.
[0006] The technical solution of the present invention: A method for preparing modified fusible polytetrafluoroethylene comprises the following steps: S1: subjecting the fusible polytetrafluoroethylene to low-temperature pulverization treatment with liquid nitrogen to obtain pulverized fusible polytetrafluoroethylene; S2: using the fusible polytetrafluoroethylene crushed in the dopamine surface modification step S1, and mixing it with the compound to obtain a fusible polytetrafluoroethylene composition; S3: high-temperature coating the composite nano-silicon dioxide and the fusible polytetrafluoroethylene composition in step S2 to obtain modified fusible polytetrafluoroethylene; The compound is prepared by modifying naringin and montmorillonite with aminosilane; The composite nano silicon dioxide is prepared by coating nano silicon dioxide with cellulose nanofibers and then mixing the nano silicon dioxide with pyrogallol-polyethyleneimine polymer.
[0007] Furthermore, in step S1, the process parameters of the liquid nitrogen low-temperature pulverization treatment are: the cooling medium is 0.6-1 MPa liquid nitrogen, the liquid nitrogen pulverization temperature is minus 196-minus 150°C, the total power is 15-16KW, and the pulverization speed is 600-700r / min.
[0008] Furthermore, in step S1, the particle size of the crushed fusible polytetrafluoroethylene is 80-120 μm.
[0009] Furthermore, in step S1, the fusible polytetrafluoroethylene material is subjected to a low-temperature crushing treatment with liquid nitrogen, so that the fusible polytetrafluoroethylene is quickly frozen to a brittle state, and a layer of ice crystals is generated on its surface, which increases the hardness of the material. In addition, under the combined effects of repeated impacts, collisions, shearing and friction between the material and the blades and gears, and between the material and the material, the material containing ice crystals on the surface is easy to crush, thereby obtaining a powder material with finer particle size and good dispersibility.
[0010] Furthermore, step S2 is specifically as follows: A1: Add the fusible polytetrafluoroethylene crushed in step S1 into Tris-HCl buffer, stir evenly, then add dopamine, stir for 3-5 hours, filter, wash and dry to obtain an intermediate product; A2: Add naringin and montmorillonite to deionized water and stir for 40-50 minutes to obtain a dispersion, add aminosilane to ethanol and deionized water, stir evenly, add acetic acid to adjust the pH value of the solution to 3-4 to obtain a silane solution, add the silane solution to the dispersion, stir at 60-80°C for 0.5-1h, filter, wash and dry to obtain a composite; A3: Add the intermediate product and the compound into ethanol, stir evenly, then add hydrochloric acid solution, stir and react for 10-20 minutes, filter, wash and dry to obtain a fusible polytetrafluoroethylene composition.
[0011] In the above reaction process, in step A1, dopamine can self-polymerize on the surface of the crushed fusible polytetrafluoroethylene to form a polydopamine layer to obtain an intermediate product, so that the surface of the crushed fusible polytetrafluoroethylene has hydroxyl groups, which is conducive to coating the shielding layer on the surface of the crushed fusible polytetrafluoroethylene and improving the partial discharge resistance of the fusible polytetrafluoroethylene; in step A2, both naringin and montmorillonite contain a large number of hydroxyl groups, which can be combined with the silanol groups generated by the hydrolysis of aminosilane, and naringin contains Some phenol structures can combine with montmorillonite through hydrogen bonds, further improving the dispersibility of montmorillonite in the aminosilane system, and grafting aminosilane onto naringin and montmorillonite to form a composite; in step A3, the amino group on the aminosilane in the composite can combine with the hydroxyl group on the surface of the intermediate product, so that the composite forms a shielding layer on the surface of the intermediate product, thereby improving the partial discharge resistance of the fusible polytetrafluoroethylene and avoiding charge accumulation of the fusible polytetrafluoroethylene, which leads to partial discharge breakdown and damage to the fusible polytetrafluoroethylene.
[0012] Furthermore, in step A1, the mass ratio of the crushed fusible polytetrafluoroethylene, Tris-HCl buffer, and dopamine is 0.5-1.5:45-55:0.3-0.7.
[0013] Furthermore, in step A2, the mass ratio of naringin, montmorillonite and deionized water is 1.1-1.3:1.1-1.3:25-35.
[0014] Furthermore, in step A2, the mass ratio of the aminosilane, ethanol, deionized water and acetic acid is 0.1-0.3:15-25:10-20:0.3-0.7.
[0015] Furthermore, in step A2, the aminosilane is γ-aminopropyltriethoxysilane.
[0016] Furthermore, in step A3, the mass ratio of the intermediate product, the compound, ethanol and the hydrochloric acid solution is 8-12: 1-1.4: 80-120: 0.05-0.15.
[0017] Furthermore, in step S3, the power of the high-temperature coating equipment is 2-2.2KW, the rotation speed is 20-107rpm, the heating power is 5-10KW, the loading amount is 6-10L, and the heating temperature is 85-175°C.
[0018] Furthermore, in step S3, the mass ratio of the composite nano-silicon dioxide to the fusible polytetrafluoroethylene composition is 0.8-1.2:1-1.4.
[0019] Furthermore, the preparation method of composite nano-silicon dioxide comprises the following steps: B1: Add cellulose nanofibers to ethanol, stir until completely dissolved, then add nano-silicon dioxide and hydrochloric acid solution, stir and react at 45-55°C for 30-40 minutes, filter, wash and dry to obtain pretreated nano-silicon dioxide; B2: Add pyrogallol and polyethyleneimine to a Tris-HCl buffer solution with a pH value of 8.6-9, stir until completely dissolved, seal, stir in a 40-50° C. water bath for 5-7 hours, and filter to obtain a pyrogallol-polyethyleneimine polymer; B3: Mix the pyrogallol-polyethyleneimine polymer and the pretreated nano-silica, stir evenly, heat to 35-45°C, stir and react at a speed of 350-450r / min for 0.5-1.5h, cool to room temperature, filter, wash and dry to obtain composite nano-silica.
[0020] In the above reaction process, in step B1, the hydroxyl groups on the cellulose nanofibers can be combined with the hydroxyl groups on the surface of the nano-silica, so that the cellulose nanofibers are coated on the surface of the nano-silica to obtain pretreated nano-silica; in step B2, the hydroxyl groups in pyrogallol are combined with the amino groups in polyethyleneimine through an electrostatic reaction, and the hydroxyl groups of pyrogallol are partially self-oxidized to carbonyl groups in a Tris-HCl buffer solution, and are combined with the amino groups of polyethyleneimine through a Schiff base reaction to form a pyrogallol-polyethyleneimine polymer; in step B3, the hydroxyl groups on the pretreated nano-silica can be combined with the polar functional groups of the pyrogallol-polyethyleneimine polymer through chemical bonds, so that the pyrogallol-polyethyleneimine polymer is cross-linked, and the cross-linked network structure is entangled on the surface of the pretreated nano-silica to form a core-shell structure, thereby further improving the binding force between the nano-silica and the polytetrafluoroethylene powder.
[0021] Furthermore, in step B1, the mass ratio of the cellulose nanofibers, ethanol, nano-silicon dioxide, and hydrochloric acid solution is 0.7-0.8:25-35:0.3-0.7:0.1-0.3.
[0022] Furthermore, in step B2, the mass ratio of pyrogallol, polyethyleneimine, and Tris-HCl buffer is 4-6:1.2-1.3:80-120.
[0023] Furthermore, in step B3, the mass ratio of the pyrogallol-polyethyleneimine polymer to the pretreated nano-silica is 0.5-1:0.4-0.8.
[0024] The present invention has the following beneficial effects: (1) In the technical solution of the present invention, montmorillonite has excellent insulation performance and can effectively prevent the passage of current, thereby reducing local discharge. It also has high breakdown strength and can maintain stable insulation performance under high electric field strength. It is not easy to have breakdown, thereby reducing local discharge. Aminosilane is grafted onto naringin and montmorillonite. The phenol structure contained in naringin can be combined with montmorillonite through hydrogen bonds, further improving the dispersibility of montmorillonite in the aminosilane system and preventing the montmorillonite from falling off. The composite is grafted onto the surface of dopamine through chemical bonds to modify the crushed fusible polytetrafluoroethylene. The naringin in the compound will form a melt during the high-temperature coating process and fill the pores on the contact surface of the nano-silica and the polytetrafluoroethylene to form a denser interface layer, thereby enhancing the bonding force between the nano-silica and the polytetrafluoroethylene powder, improving the mechanical properties and wear resistance of the modified fusible polytetrafluoroethylene, reducing the porosity of the modified fusible polytetrafluoroethylene, and improving the resistance to partial discharge.
[0025] (2) In the technical scheme of the present invention, cellulose nanofibers are coated on the surface of nano-silica to give it reactive functional groups, and a flexible protective film can be formed on the surface of nano-silica to improve the coating effect of nano-silica; pyrogallol and polyethyleneimine form pyrogallol-polyethyleneimine polymer, which has good mechanical properties and adhesion properties after condensation; pretreated nano-silica and pyrogallol-polyethyleneimine polymer are combined by chemical bonds, so that the pyrogallol-polyethyleneimine polymer is cross-linked, and the formed cross-linked network structure is entangled on the surface of pretreated nano-silica to form a core-shell structure, which can adhere nano-silica to the surface of polytetrafluoroethylene powder by physical methods, thereby improving the bonding force between nano-silica and polytetrafluoroethylene powder.
[0026] (3) In the technical solution of the present invention, the cross-linked network structure contained in the composite nano-silica forms a pyrogallol-polyethyleneimine polymer layer on the surface of the polytetrafluoroethylene powder. As a lubricating component, the polymer layer can reduce the friction coefficient and improve the lubricity, thereby improving the lubricity of the modified fusible polytetrafluoroethylene.
[0027] (4) In the technical solution of the present invention, after the fusible polytetrafluoroethylene is treated with liquid nitrogen low-temperature pulverization, the material containing ice crystals on the surface of the fusible polytetrafluoroethylene is easy to pulverize, and it is easier to obtain fusible polytetrafluoroethylene powder with finer particle size and good dispersibility; the liquid nitrogen low-temperature pulverization treatment can avoid the discoloration and denaturation of the material caused by the heat generated by friction in a low-temperature environment, reduce the contact between the material and the air, and reduce the occurrence of oxidation reactions. The composite nano-silica and the fusible polytetrafluoroethylene composition are coated at high temperature, and the excellent adhesion of the composite nano-silica can be well adhered to the surface of the fusible polytetrafluoroethylene composition, and the shielding layer on the surface of the fusible polytetrafluoroethylene composition can also be combined with the composite nano-silica through chemical bonds, further improving its interfacial bonding strength. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The specific parameters of the raw materials used in the present invention are as follows: Fusible polytetrafluoroethylene: The molecular weight is usually 1×10 5 -1.6×10 6 , provided by Hubei Jusheng Technology Co., Ltd., with a particle size of 1-3mm; nano-silicon dioxide: provided by Xuancheng Jingrui New Materials Co., Ltd., with a particle size of 50-80nm; dopamine: CAS No.: 51-61-6, provided by Shanghai Aladdin Biochemical Technology Co., Ltd.; naringin: CAS No.: 10236-47-2, provided by Shanghai Aladdin Biochemical Technology Co., Ltd.; cellulose nanofibers: provided by Zhejiang Shansi Technology Co., Ltd., with a diameter of 10-30nm and a length of 0.2-1μm; pyrogallol: CAS No.: 87-66-1, provided by Shanghai Aladdin Biochemical Technology Co., Ltd.; polyethyleneimine: CAS No.: 9002-98-6, provided by Shanghai Aladdin Biochemical Technology Co., Ltd.; montmorillonite: sodium montmorillonite, CAS No.: 1318-93-0, provided by Shanghai McLean Biochemical Technology Co., Ltd.
[0030] Example 1 A method for preparing modified fusible polytetrafluoroethylene comprises the following steps: S1: subjecting fusible polytetrafluoroethylene to low-temperature pulverization treatment with liquid nitrogen to obtain pulverized fusible polytetrafluoroethylene; wherein, the process parameters of the liquid nitrogen low-temperature pulverization treatment are: the equipment model is MCM250, the cooling medium is 0.6mpa liquid nitrogen, the liquid nitrogen pulverization temperature is minus 196°C, the total power is 15KW, and the pulverization speed is 600r / min; the particle size of the pulverized fusible polytetrafluoroethylene is 80μm; S2: preparing a fusible polytetrafluoroethylene composition, the specific steps are: A1: According to the mass ratio of crushed fusible polytetrafluoroethylene, Tris-HCl buffer and dopamine being 0.5:45:0.3, the crushed fusible polytetrafluoroethylene in step S1 is added to Tris-HCl buffer with a pH value of 8, stirred evenly, and then dopamine is added, stirred for 3 hours, filtered, washed with ethanol and deionized water three times respectively (the mass of ethanol and deionized water each time is 80% of the mass of Tris-HCl buffer), and dried at 70°C for 10 minutes to obtain an intermediate product; A2: According to the mass ratio of naringin, montmorillonite and deionized water of 1.1:1.1:25, naringin and montmorillonite were added to deionized water and stirred for 40 minutes to obtain a dispersion; according to the mass ratio of γ-aminopropyltriethoxysilane, ethanol, deionized water and acetic acid of 0.1:15:10:0.3, γ-aminopropyltriethoxysilane was added to ethanol and deionized water, stirred evenly, and then 93% acetic acid was added to adjust the pH value of the solution to 3 to obtain a silane solution; the silane solution was added to the dispersion, stirred at 60°C for 0.5h, filtered, washed with deionized water (the mass of deionized water is 10 times the mass of naringin), and dried at 60°C for 15min to obtain a composite; A3: According to the mass ratio of the intermediate product, the compound, ethanol and the hydrochloric acid solution of 8:1:80:0.05, the intermediate product and the compound are added to ethanol, stirred evenly, and then a hydrochloric acid solution with a mass fraction of 50% is added, stirred and reacted for 10 minutes, filtered, washed with deionized water (the mass of deionized water is 50% of the mass of ethanol), and dried at 60°C for 15 minutes to obtain a fusible polytetrafluoroethylene composition; S3: According to the mass ratio of the composite nano-silicon dioxide and the fusible polytetrafluoroethylene composition of 0.8:1, the composite nano-silicon dioxide and the fusible polytetrafluoroethylene composition are placed in a mixing cylinder, and high-temperature coating is performed to obtain modified fusible polytetrafluoroethylene; wherein the high-temperature coating equipment model is VCJ / 15, the power is 2KW, the speed is 20rpm, the heating power is 5KW, the loading amount is 6L, and the heating temperature is 85℃; The preparation method of composite nano silicon dioxide comprises the following steps: B1: According to the mass ratio of cellulose nanofibers, ethanol, nano-silica and hydrochloric acid solution of 0.7:25:0.3:0.1, cellulose nanofibers were added to ethanol and stirred until completely dissolved, and then nano-silica and 35% hydrochloric acid solution were added, stirred and reacted at 45°C for 30 minutes, filtered, washed with deionized water (the mass of deionized water is equal to that of ethanol), and dried at 60°C for 10 minutes to obtain pretreated nano-silica; B2: Pyrogallol and polyethyleneimine were added to a Tris-HCl buffer solution with a pH value of 8.6 according to a mass ratio of 4:1.2:80, stirred until completely dissolved, sealed, stirred in a 40°C water bath for 5 h, and filtered to obtain a pyrogallol-polyethyleneimine polymer; B3: According to the mass ratio of pyrogallol-polyethyleneimine polymer and pretreated nano-silica being 0.5:0.4, pyrogallol-polyethyleneimine polymer and pretreated nano-silica were mixed and stirred evenly, heated to 35°C, stirred and reacted at a speed of 350r / min for 1.5h, cooled to room temperature, filtered, washed with deionized water (the mass of deionized water is 3 times the mass of pyrogallol-polyethyleneimine polymer), and dried at 60°C for 10min to obtain composite nano-silica.
[0031] Example 2 A method for preparing modified fusible polytetrafluoroethylene comprises the following steps: S1: subjecting fusible polytetrafluoroethylene to low-temperature pulverization treatment with liquid nitrogen to obtain pulverized fusible polytetrafluoroethylene; wherein, the process parameters of the liquid nitrogen low-temperature pulverization treatment are: the equipment model is MCM250, the cooling medium is 0.8mpa liquid nitrogen, the liquid nitrogen pulverization temperature is minus 175°C, the total power is 15.5KW, and the pulverization speed is 650r / min; the particle size of the pulverized fusible polytetrafluoroethylene is 100μm; S2: preparing a fusible polytetrafluoroethylene composition, the specific steps are: A1: According to the mass ratio of crushed fusible polytetrafluoroethylene, Tris-HCl buffer and dopamine being 1:50:0.5, the crushed fusible polytetrafluoroethylene in step S1 is added to Tris-HCl buffer with a pH value of 8.5, stirred evenly, and then dopamine is added, stirred for 4 hours, filtered, washed with ethanol and deionized water three times respectively (the mass of ethanol and deionized water each time is 80% of the mass of Tris-HCl buffer), and dried at 70°C for 10 minutes to obtain an intermediate product; A2: According to the mass ratio of naringin, montmorillonite and deionized water of 1.2:1.2:30, naringin and montmorillonite were added to deionized water and stirred for 45 minutes to obtain a dispersion; according to the mass ratio of γ-aminopropyltriethoxysilane, ethanol, deionized water and acetic acid of 0.2:20:15:0.5, γ-aminopropyltriethoxysilane was added to ethanol and deionized water, stirred evenly, and then 95% acetic acid was added to adjust the pH value of the solution to 3.5 to obtain a silane solution; the silane solution was added to the dispersion, stirred at 70°C for 0.7h, filtered, washed with deionized water (the mass of deionized water is 10 times the mass of naringin), and dried at 60°C for 15min to obtain a composite; A3: According to the mass ratio of the intermediate product, the compound, ethanol and the hydrochloric acid solution of 10:1.2:100:0.1, the intermediate product and the compound are added to ethanol, stirred evenly, and then a hydrochloric acid solution with a mass fraction of 60% is added, stirred and reacted for 15 minutes, filtered, washed with deionized water (the mass of deionized water is 50% of the mass of ethanol), and dried at 60°C for 15 minutes to obtain a fusible polytetrafluoroethylene composition; S3: According to the mass ratio of the composite nano-silicon dioxide and the fusible polytetrafluoroethylene composition of 1:1.2, the composite nano-silicon dioxide and the fusible polytetrafluoroethylene composition are placed in a mixing cylinder, and high-temperature coating is performed to obtain modified fusible polytetrafluoroethylene; wherein the high-temperature coating equipment model is VCJ / 15, the power is 2.1KW, the rotation speed is 60rpm, the heating power is 7.5KW, the loading amount is 8L, and the heating temperature is 130℃; The preparation method of composite nano silicon dioxide comprises the following steps: B1: According to the mass ratio of cellulose nanofibers, ethanol, nano-silica and hydrochloric acid solution of 0.75:30:0.5:0.2, cellulose nanofibers were added to ethanol and stirred until completely dissolved, and then nano-silica and 36% hydrochloric acid solution were added, stirred and reacted at 50°C for 35 minutes, filtered, washed with deionized water (the mass of deionized water is equal to that of ethanol), and dried at 60°C for 10 minutes to obtain pretreated nano-silica; B2: According to the mass ratio of pyrogallol, polyethyleneimine and Tris-HCl buffer of 5:1.25:100, pyrogallol and polyethyleneimine were added to Tris-HCl buffer with a pH value of 8.8, stirred until completely dissolved, sealed, stirred in a water bath at 45°C for 6 hours, and filtered to obtain pyrogallol-polyethyleneimine polymer; B3: According to the mass ratio of pyrogallol-polyethyleneimine polymer and pretreated nano-silica being 0.8:0.6, pyrogallol-polyethyleneimine polymer and pretreated nano-silica were mixed and stirred evenly, heated to 40°C, stirred and reacted at a speed of 400r / min for 1h, cooled to room temperature, filtered, washed with deionized water (the mass of deionized water is 3 times the mass of pyrogallol-polyethyleneimine polymer), and dried at 60°C for 10min to obtain composite nano-silica.
[0032] Example 3 A method for preparing modified fusible polytetrafluoroethylene comprises the following steps: S1: subjecting fusible polytetrafluoroethylene to low-temperature pulverization treatment with liquid nitrogen to obtain pulverized fusible polytetrafluoroethylene; wherein, the process parameters of the liquid nitrogen low-temperature pulverization treatment are: the equipment model is MCM250, the cooling medium is 1mpa liquid nitrogen, the liquid nitrogen pulverization temperature is minus 150°C, the total power is 16KW, and the pulverization speed is 700r / min; the particle size of the pulverized fusible polytetrafluoroethylene is 120μm; S2: preparing a fusible polytetrafluoroethylene composition, the specific steps are: A1: According to the mass ratio of crushed fusible polytetrafluoroethylene, Tris-HCl buffer and dopamine being 1.5:55:0.7, the crushed fusible polytetrafluoroethylene in step S1 is added to Tris-HCl buffer with a pH value of 9, stirred evenly, and then dopamine is added, stirred for 5 hours, filtered, washed with ethanol and deionized water three times respectively (the mass of ethanol and deionized water each time is 80% of the mass of Tris-HCl buffer), and dried at 70°C for 10 minutes to obtain an intermediate product; A2: According to the mass ratio of naringin, montmorillonite and deionized water of 1.3:1.3:35, naringin and montmorillonite were added to deionized water and stirred for 50 minutes to obtain a dispersion; according to the mass ratio of γ-aminopropyltriethoxysilane, ethanol, deionized water and acetic acid of 0.3:25:20:0.7, γ-aminopropyltriethoxysilane was added to ethanol and deionized water, stirred evenly, and then 96% acetic acid was added to adjust the pH value of the solution to 4 to obtain a silane solution; the silane solution was added to the dispersion, stirred at 80°C for 1 hour, filtered, washed with deionized water (the mass of deionized water is 10 times the mass of naringin), and dried at 60°C for 15 minutes to obtain a composite; A3: According to the mass ratio of the intermediate product, compound, ethanol and hydrochloric acid solution of 12:1.4:120:0.15, the intermediate product and compound are added to ethanol, stirred evenly, and then a hydrochloric acid solution with a mass fraction of 70% is added, stirred and reacted for 20 minutes, filtered, washed with deionized water (the mass of deionized water is 50% of the mass of ethanol), and dried at 60°C for 15 minutes to obtain a fusible polytetrafluoroethylene composition; S3: According to the mass ratio of the composite nano-silicon dioxide and the fusible polytetrafluoroethylene composition of 1.2:1.4, the composite nano-silicon dioxide and the fusible polytetrafluoroethylene composition are placed in a mixing cylinder for high-temperature coating to obtain modified fusible polytetrafluoroethylene; wherein the high-temperature coating equipment model is VCJ / 15, the power is 2.2KW, the rotation speed is 107rpm, the heating power is 10KW, the loading amount is 10L, and the heating temperature is 175℃; The preparation method of composite nano silicon dioxide comprises the following steps: B1: According to the mass ratio of cellulose nanofibers, ethanol, nano-silica and hydrochloric acid solution of 0.8:35:0.7:0.3, cellulose nanofibers were added to ethanol and stirred until completely dissolved, and then nano-silica and 37% hydrochloric acid solution were added, stirred and reacted at 55°C for 40 minutes, filtered, washed with deionized water (the mass of deionized water is equal to that of ethanol), and dried at 60°C for 10 minutes to obtain pretreated nano-silica; B2: Pyrogallol and polyethyleneimine were added to a Tris-HCl buffer solution with a pH value of 9 according to a mass ratio of pyrogallol, polyethyleneimine, and Tris-HCl buffer of 6:1.3:120, stirred until completely dissolved, sealed, stirred in a 50°C water bath for 7 hours, and filtered to obtain a pyrogallol-polyethyleneimine polymer; B3: According to the mass ratio of pyrogallol-polyethyleneimine polymer and pretreated nano-silica being 1:0.8, pyrogallol-polyethyleneimine polymer and pretreated nano-silica were mixed and stirred evenly, heated to 45°C, stirred and reacted at a speed of 450r / min for 0.5h, cooled to room temperature, filtered, washed with deionized water (the mass of deionized water is 3 times the mass of pyrogallol-polyethyleneimine polymer), and dried at 60°C for 10min to obtain composite nano-silica.
[0033] Comparative Example 1 The difference between this comparative example and Example 3 is that when preparing the fusible polytetrafluoroethylene composition, the mass of the compound in step A2 is replaced by naringin and montmorillonite, and then directly mixed with the intermediate product, and the remaining steps and raw materials are synchronized with Example 3; S2: preparing a fusible polytetrafluoroethylene composition, the specific steps are: A1: According to the mass ratio of crushed fusible polytetrafluoroethylene, Tris-HCl buffer and dopamine being 1.5:55:0.7, the crushed fusible polytetrafluoroethylene in step S1 is added to Tris-HCl buffer with a pH value of 9, stirred evenly, and then dopamine is added, stirred for 5 hours, filtered, washed with ethanol and deionized water three times respectively (the mass of ethanol and deionized water each time is 80% of the mass of Tris-HCl buffer), and dried at 70°C for 10 minutes to obtain an intermediate product; A2: According to the mass ratio of the intermediate product, naringin, montmorillonite, ethanol and hydrochloric acid solution of 12:0.7:0.7:120:0.15, the intermediate product and naringin are added to ethanol, stirred evenly, and then a hydrochloric acid solution with a mass fraction of 70% is added, stirred for reaction for 20 minutes, filtered, washed with deionized water (the mass of deionized water is 50% of the mass of ethanol), and dried at 60°C for 15 minutes to obtain a fusible polytetrafluoroethylene composition.
[0034] Comparative Example 2 The difference between this comparative example and Example 3 is that when preparing the modified fusible polytetrafluoroethylene, the crushed fusible polytetrafluoroethylene is directly combined with the composite nano-silicon dioxide, and the remaining steps and raw materials are the same as those of Example 3; A method for preparing modified fusible polytetrafluoroethylene comprises the following steps: S1: subjecting fusible polytetrafluoroethylene to low-temperature pulverization treatment with liquid nitrogen to obtain pulverized fusible polytetrafluoroethylene; wherein, the process parameters of the liquid nitrogen low-temperature pulverization treatment are: the equipment model is MCM250, the cooling medium is 1mpa liquid nitrogen, the liquid nitrogen pulverization temperature is minus 150°C, the total power is 16KW, and the pulverization speed is 700r / min; the particle size of the pulverized fusible polytetrafluoroethylene is 120μm; S2: According to the mass ratio of composite nano-silicon dioxide and crushed fusible polytetrafluoroethylene of 1.2:1.4, the composite nano-silicon dioxide and the crushed fusible polytetrafluoroethylene are placed in a mixing cylinder for high-temperature coating to obtain modified fusible polytetrafluoroethylene; wherein, the high-temperature coating equipment model is VCJ / 15, the power is 2.2KW, the rotation speed is 107rpm, the heating power is 10KW, the loading amount is 10L, and the heating temperature is 175℃; The preparation method of composite nano silicon dioxide comprises the following steps: B1: According to the mass ratio of cellulose nanofibers, ethanol, nano-silica and hydrochloric acid solution of 0.8:35:0.7:0.3, cellulose nanofibers were added to ethanol and stirred until completely dissolved, and then nano-silica and 37% hydrochloric acid solution were added, stirred and reacted at 55°C for 40 minutes, filtered, washed with deionized water (the mass of deionized water is equal to that of ethanol), and dried at 60°C for 10 minutes to obtain pretreated nano-silica; B2: Pyrogallol and polyethyleneimine were added to a Tris-HCl buffer solution with a pH value of 9 according to a mass ratio of pyrogallol, polyethyleneimine, and Tris-HCl buffer of 6:1.3:120, stirred until completely dissolved, sealed, stirred in a 50°C water bath for 7 hours, and filtered to obtain a pyrogallol-polyethyleneimine polymer; B3: According to the mass ratio of pyrogallol-polyethyleneimine polymer and pretreated nano-silica being 1:0.8, pyrogallol-polyethyleneimine polymer and pretreated nano-silica were mixed and stirred evenly, heated to 45°C, stirred and reacted at a speed of 450r / min for 0.5h, cooled to room temperature, filtered, washed with deionized water (the mass of deionized water is 3 times the mass of pyrogallol-polyethyleneimine polymer), and dried at 60°C for 10min to obtain composite nano-silica.
[0035] Comparative Example 3 The difference between this comparative example and Example 3 is that when preparing composite nano-silicon dioxide, the mass of pre-treated nano-silicon dioxide in step B1 is replaced by nano-silicon dioxide, and the remaining steps and raw materials are synchronized with Example 3; The preparation method of composite nano silicon dioxide comprises the following steps: B1: Pyrogallol and polyethyleneimine were added to a Tris-HCl buffer solution with a pH value of 9 according to a mass ratio of pyrogallol, polyethyleneimine, and Tris-HCl buffer of 6:1.3:120, stirred until completely dissolved, sealed, stirred in a 50°C water bath for 7 hours, and filtered to obtain a pyrogallol-polyethyleneimine polymer; B2: According to the mass ratio of pyrogallol-polyethyleneimine polymer to nano-silica being 1:0.8, pyrogallol-polyethyleneimine polymer and nano-silica were mixed and stirred evenly, heated to 45°C, stirred and reacted at a speed of 450r / min for 0.5h, cooled to room temperature, filtered, washed with deionized water (the mass of deionized water is 3 times the mass of pyrogallol-polyethyleneimine polymer), and dried at 60°C for 10min to obtain composite nano-silica.
[0036] Comparative Example 4 The difference between this comparative example and Example 3 is that when preparing composite nano-silica, the mass of the pyrogallol-polyethyleneimine polymer in step B2 is replaced by polyethyleneimine, and the remaining steps and raw materials are synchronized with Example 3; The preparation method of composite nano silicon dioxide comprises the following steps: B1: According to the mass ratio of cellulose nanofibers, ethanol, nano-silica and hydrochloric acid solution of 0.8:35:0.7:0.3, cellulose nanofibers were added to ethanol and stirred until completely dissolved, and then nano-silica and 37% hydrochloric acid solution were added, stirred and reacted at 55°C for 40 minutes, filtered, washed with deionized water (the mass of deionized water is equal to that of ethanol), and dried at 60°C for 10 minutes to obtain pretreated nano-silica; B2: According to the mass ratio of polyethyleneimine to pretreated nano-silica of 1:0.8, polyethyleneimine and pretreated nano-silica were mixed and stirred evenly, heated to 45°C, stirred and reacted at a speed of 450 r / min for 1.5 hours, cooled to room temperature, filtered, washed and dried to obtain composite nano-silica.
[0037] The performance of the modified fusible polytetrafluoroethylene prepared in Examples 1-3 and Comparative Examples 1-4 is now tested.
[0038] Wear resistance test: The modified fusible polytetrafluoroethylene powder prepared in Examples 1-3 and Comparative Examples 1-4 was ground with a bearing steel ball (φ=4mm). The steel ball was fixed on the sensor and in close contact with the surface of the sample. The sample was fixed on the test bench and rotated with the test bench. Under the principle of relative motion, the steel ball rotated on the surface of the sample and left wear marks. The rotation line speed selected for the test was 200r / min, the rotation radius was 3mm, the positive pressure applied was 2N, and the width and depth of the wear marks were measured; the friction coefficient was tested using a controlled environment friction and wear tester UMT; Mechanical performance tests include tensile performance tests and bending performance tests. Tensile performance tests are conducted according to GB / T 1040.1-2006, and bending performance tests are conducted according to GB / T 9341-2008. INSTRONG universal testing machine is used for testing. Partial discharge resistance test: According to GJB 973A-2004 standard, the corona extinction voltage of the modified fusible polytetrafluoroethylene prepared in Examples 1-3 and Comparative Examples 1-4 was measured to characterize its partial discharge resistance. The test results are shown in Tables 1 and 2 below: Table 1 Performance parameters of modified fusible polytetrafluoroethylene prepared in Examples 1-3 and Comparative Examples 1-4
[0039] Table 2 Partial discharge resistance of modified fusible polytetrafluoroethylene prepared in Examples 1-3 and Comparative Examples 1-4
[0040] It can be seen from the data in Table 1 and Table 2 above that, by comparing Comparative Example 1 with Example 3, the mass of the composite in step A2 is replaced with naringin and montmorillonite, and then directly mixed with the intermediate product to prepare a fusible polytetrafluoroethylene composition, and then coated with composite nano-silica to obtain a modified fusible polytetrafluoroethylene, the partial discharge resistance, mechanical properties and wear resistance of which are worse than those of Example 3, indicating that the naringin and montmorillonite in the composite can be grafted on the surface of the fusible polytetrafluoroethylene after dopamine modification and crushing through chemical bonds after aminosilane modification to form a shielding layer, thereby avoiding charge accumulation of the fusible polytetrafluoroethylene, resulting in partial discharge breakdown and destruction of the fusible polytetrafluoroethylene, so that the modified fusible polytetrafluoroethylene has better partial discharge resistance, and its mechanical properties and wear resistance are also better; From the comparison between Comparative Example 2 and Example 3, it can be seen that the modified fusible polytetrafluoroethylene prepared by directly combining the crushed fusible polytetrafluoroethylene with the composite nano-silica has poorer local discharge resistance and wear resistance than Example 3, indicating that the naringin in the composite can form a melt during the high-temperature coating process, and is evenly filled into the pores of the contact surface between the nano-silica and the polytetrafluoroethylene together with the montmorillonite, forming a denser and more strongly bonded interface layer, further improving the mechanical properties, wear resistance and local discharge resistance of the modified fusible polytetrafluoroethylene; From the comparison between Comparative Example 3 and Example 3, it can be seen that the composite nano-silica prepared by replacing the mass of the pretreated nano-silica in step B1 with nano-silica is used to coat the fusible polytetrafluoroethylene composition, and finally the modified fusible polytetrafluoroethylene is obtained, and its mechanical properties are worse than those of Example 3, indicating that the cellulose nanofibers can form a flexible protective film on the surface of the nano-silica, improve the coating effect of the nano-silica, and thus enhance the mechanical properties and wear resistance of the modified fusible polytetrafluoroethylene; By comparing Comparative Example 4 with Example 3, it can be seen that the fusible polytetrafluoroethylene composition is coated with the composite nano-silica prepared by replacing the mass of the pyrogallol-polyethyleneimine polymer in step B2 with polyethyleneimine, and finally obtaining a modified fusible polytetrafluoroethylene, whose wear resistance and mechanical properties are worse than those of Example 3, indicating that pyrogallol and polyethyleneimine form a pyrogallol-polyethyleneimine polymer, which has good mechanical properties and adhesion after coagulation, and can adhere nano-silica to the surface of the polytetrafluoroethylene powder by physical methods, thereby improving the coating effect and enhancing the mechanical properties. In addition, the pyrogallol-polyethyleneimine polymer layer, as a lubricating component, can reduce the friction coefficient, further improving the lubricity of the modified fusible polytetrafluoroethylene.
[0041] It can be seen from Table 1 and Table 2 above that the modified fusible polytetrafluoroethylene prepared in Examples 1-3, compared with the modified fusible polytetrafluoroethylene prepared in Comparative Examples 1-4, is prepared by subjecting the fusible polytetrafluoroethylene to low-temperature pulverization with liquid nitrogen, then surface modification with dopamine, and then mixing with a compound to obtain a fusible polytetrafluoroethylene composition, and finally high-temperature coating with composite nano-silicon dioxide to obtain the modified fusible polytetrafluoroethylene, which meets the test performance requirements, while the modified fusible polytetrafluoroethylene prepared in Comparative Examples 1-4 does not meet the performance requirements. This shows that the modified fusible polytetrafluoroethylene prepared by the present invention has good mechanical properties, wear resistance and partial discharge resistance, and its comprehensive performance is good, which expands its application range.
[0042] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0043] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing modified fusible polytetrafluoroethylene, characterized in that: The following steps are involved: S1: subjecting the fusible polytetrafluoroethylene to low-temperature pulverization treatment with liquid nitrogen to obtain pulverized fusible polytetrafluoroethylene; S2: using the fusible polytetrafluoroethylene crushed in the dopamine surface modification step S1, and mixing it with the compound to obtain a fusible polytetrafluoroethylene composition; S3: high-temperature coating the composite nano-silicon dioxide and the fusible polytetrafluoroethylene composition in step S2 to obtain modified fusible polytetrafluoroethylene; The compound is prepared by modifying naringin and montmorillonite with aminosilane; The composite nano silicon dioxide is prepared by coating nano silicon dioxide with cellulose nanofibers and then mixing the nano silicon dioxide with pyrogallol-polyethyleneimine polymer.
2. The method for preparing modified fusible polytetrafluoroethylene according to claim 1, characterized in that: In step S1, the process parameters of the liquid nitrogen low-temperature pulverization treatment are: the cooling medium is 0.6-1 MPa liquid nitrogen, the liquid nitrogen pulverization temperature is minus 196-minus 150°C, the total power is 15-16KW, and the pulverization speed is 600-700r / min.
3. The method for preparing modified fusible polytetrafluoroethylene according to claim 1, characterized in that: In step S1, the particle size of the crushed fusible polytetrafluoroethylene is 80-120 μm.
4. The method for preparing modified fusible polytetrafluoroethylene according to claim 1, characterized in that: Step S2 is specifically as follows: A1: Add the fusible polytetrafluoroethylene crushed in step S1 into Tris-HCl buffer, stir evenly, then add dopamine, stir for 3-5 hours, filter, wash and dry to obtain an intermediate product; A2: Add naringin and montmorillonite to deionized water and stir for 40-50 minutes to obtain a dispersion, add aminosilane to ethanol and deionized water, stir evenly, add acetic acid to adjust the pH value of the solution to 3-4 to obtain a silane solution, add the silane solution to the dispersion, stir at 60-80°C for 0.5-1h, filter, wash and dry to obtain a composite; A3: Add the intermediate product and the compound into ethanol, stir evenly, then add hydrochloric acid solution, stir and react for 10-20 minutes, filter, wash and dry to obtain a fusible polytetrafluoroethylene composition.
5. The method for preparing modified fusible polytetrafluoroethylene according to claim 4, characterized in that: In step A1, the mass ratio of the crushed fusible polytetrafluoroethylene, Tris-HCl buffer, and dopamine is 0.5-1.5:45-55:0.3-0.7; In step A2, the mass ratio of aminosilane, ethanol, deionized water and acetic acid is 0.1-0.3:15-25:10-20:0.3-0.7; In step A3, the mass ratio of the intermediate product, the compound, ethanol and the hydrochloric acid solution is 8-12:1-1.4:80-120:0.05-0.
15.
6. The method for preparing modified fusible polytetrafluoroethylene according to claim 1, characterized in that: The preparation method of the composite nano-silicon dioxide comprises the following steps: B1: Add cellulose nanofibers to ethanol, stir until completely dissolved, then add nano-silicon dioxide and hydrochloric acid solution, stir and react at 45-55°C for 30-40 minutes, filter, wash and dry to obtain pretreated nano-silicon dioxide; B2: Add pyrogallol and polyethyleneimine to a Tris-HCl buffer solution with a pH value of 8.6-9, stir until completely dissolved, seal, stir in a water bath at 40-50° C. for 5-7 hours, and filter to obtain a pyrogallol-polyethyleneimine polymer; B3: Mix the pyrogallol-polyethyleneimine polymer and the pretreated nano-silica, stir evenly, heat to 35-45°C, stir and react at a speed of 350-450r / min for 0.5-1.5h, cool to room temperature, filter, wash and dry to obtain composite nano-silica.
7. The method for preparing modified fusible polytetrafluoroethylene according to claim 6, characterized in that: In step B1, the mass ratio of the cellulose nanofibers, ethanol, nano-silicon dioxide, and hydrochloric acid solution is 0.7-0.8:25-35:0.3-0.7:0.1-0.3; In step B2, the mass ratio of pyrogallol, polyethyleneimine, and Tris-HCl buffer is 4-6:1.2-1.3:80-120; In step B3, the mass ratio of the pyrogallol-polyethyleneimine polymer to the pretreated nano-silica is 0.5-1:0.4-0.
8.
8. The method for preparing modified fusible polytetrafluoroethylene according to claim 1, characterized in that: In step S3, the power of the high-temperature coating equipment is 2-2.2KW, the rotation speed is 20-107rpm, the heating power is 5-10KW, the loading amount is 6-10L, and the heating temperature is 85-175°C.
9. The method for preparing modified fusible polytetrafluoroethylene according to claim 1, characterized in that: In step S3, the mass ratio of the composite nano-silicon dioxide to the fusible polytetrafluoroethylene composition is 0.8-1.2:1-1.
4.
10. A modified fusible polytetrafluoroethylene obtained by the preparation method according to any one of claims 1 to 9.